Building services design management - Portman, Jackie (Chichester : John Wiley & Sons Inc., 2014)
'Building services engineering design requires technical skills to ensure that the systems are safe, compliant with legislative requirements and good practices and are coordinated with the needs of the other design and construction team professionals. Design management is the business side of design, encompassing the on-going processes, business decisions, and strategies that enable innovation, and create effectively designed systems and services that ultimately enhance the quality of the built environment and should also provide organisational success to those involved'--
Machine generated contents note: Preface About the author Introduction Part One The operating context 1 The operating environment 1.1 Organisational arrangement 1.2 The internal environment 2 The external environment 2.1 Competitor analysis 2.2 PESTLE analysis 3 Engaging building services engineers 3.1 Types of commissions 3.2 Contracts 3.3 Fees 3.4 Getting work 4 Stakeholder Interfaces 4.1 The client team 4.2 Enforcing authorities 4.3 The design team 4.4 The construction team 4.5 Utility service providers 4.6 Non-contractual interfaces 5 Professional ethics Part Two Technical issues associated with building services design 6 Design criteria 6.1 External design criteria 6.2 Interior design criteria 6.3 Voluntary codes and practices 7 System descriptions 7.1 Public utility services connections 7.2 Ventilation 7.3 Heating 7.4 Cooling 7.5 Air-conditioning 7.6 Water systems 7.7 Gas systems 7.8 Electrical distribution 7.9 Artificial lighting 7.10 Controls 7.11 Lightning protection system 7.12 Fire detection and alarm system 7.13 Smoke and fire control systems 7.14 Security systems 7.15 Structured wiring system 7.16 Broadcast communications technology systems 7.17 Mobile telephony systems 7.18 Audio, visual, audiovisual and information systems 7.19 Facilities for the disabled 7.20 Vertical transportation 8 Off-site manufacturing Part Three The design management process 9 Design execution 9.1 Project stages 9.2 Design management issues 10 Risk management 11 Information management 12 Value management 13 Planning management 14 Commercial management 15 Quality management 16 Performance management Part Four Special buildings 17 Special buildings 17.1 Commercial kitchens 17.2 Hospitals and healthcare facilities 17.3 Data centres 17.4 Shopping centres 17.5 Sports facilities 17.6 Hotels 17.7 Educational buildings Index .
Includes bibliographical references and index.
Keywords: Building -- Superintendence; Construction projects -- Management; Building -- Planning; Engineering design